2021
DOI: 10.3389/fimmu.2021.659419
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cytokine Storms During Virus Infections

Abstract: Highly pathogenic virus infections usually trigger cytokine storms, which may have adverse effects on vital organs and result in high mortalities. The two cytokines interleukin (IL)-4 and interferon (IFN)-γ play key roles in the generation and regulation of cytokine storms. However, it is still unclear whether the cytokine with the largest induction amplitude is the same under different virus infections. It is unknown which is the most critical and whether there are any mathematical formulas that can fit the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 36 publications
6
55
0
Order By: Relevance
“…In contrast, airspace IFN-γ spiked dramatically between 5 and 7 dpi, in concert with the wave of lymphocytic inflammation (Figure 1e) and increasing alveolar-capillary barrier permeability (Figure 1f). These patterns of cytokine expression mimic those seen in patients suffering from severe viral illness, as detailed in a recent review (Yuan et al, 2021). As expected, the neutrophil chemokine KC (Figure 2e) and the monocyte/lymphocyte chemokine MCP-1 (Figure 2f) roughly…”
Section: Airspace Inflammatory Cytokines and Chemokines Parallel The Waves Of Cellular Inflammationsupporting
confidence: 80%
“…In contrast, airspace IFN-γ spiked dramatically between 5 and 7 dpi, in concert with the wave of lymphocytic inflammation (Figure 1e) and increasing alveolar-capillary barrier permeability (Figure 1f). These patterns of cytokine expression mimic those seen in patients suffering from severe viral illness, as detailed in a recent review (Yuan et al, 2021). As expected, the neutrophil chemokine KC (Figure 2e) and the monocyte/lymphocyte chemokine MCP-1 (Figure 2f) roughly…”
Section: Airspace Inflammatory Cytokines and Chemokines Parallel The Waves Of Cellular Inflammationsupporting
confidence: 80%
“…These include direct renal injury in the presence of acute tubular necrosis, inflammation, and cytokine storm. A study measuring cytokine storm through various viral infections showed that H1N1 infection increased the number of cytokines compared to COVID-19 [23] . Therefore, COVID-19 induces greater elevation of cytokines, resulting in a more severe disease with the risk of morbidity and/or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Besides ventilation-perfusion mismatch, intravascular coagulation and alveolar edema, COVID-19 ARDS is a very complex disease, with intrapulmonary shunting, impaired lung diffusion, inflammation, etc. [103][104][105][106][107][108][109]. We cannot expect that early oxygen therapy and pulmonary edema treatments can prevent every COVID-19 patient from the development of ARDS.…”
Section: Clinical Outlookmentioning
confidence: 99%